New commons established by pooling, facilitated by the Land Consolidation Court. Norwegian experiences and examples - Hans Sevatdal (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2016)
New commons might come into being by pooling of resources. Such pooling often needs some sort of professional external assistance, as well as appropriate institutional framework. In Norway the Land Consolidation Courts - originally established for reallocation and individualization of land and rights - have developed into a multipurpose instrument, also for facilitating common use of formerly individualized resources. Examples are extraction of certain mineral deposits, development of small-scale hydroelectric power, recreational fishing and hunting, land development etc. The issue is discussed in a context of legal framework - both in public and private law - negotiation, decision-making and enforcement.
Keywords: P48; Q15; 330; Commons; negotiations; institutions; the Land Consolidation Court